Strategic SWOT-Based Framework to Enhance Competitiveness of Islamic Financial Management Program at IAIN Parepare - Nurfadhilah; Ismayanti; Muhammad Fiqri Alif Utama; Bakhtiar Tijjang; Pandi Putra (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the competitiveness of the Islamic Financial Management Study Program of IAIN Parepare using an in-depth SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. The main focus of the study is to identify internal and external factors that influence the competitiveness of the Study Program in the ever-growing Islamic financial education industry. This study uses the EFAS (External Factory Analysis Summary) and IFAS (Internal Factor Analysis Summary) methods to assess the strengths, weaknesses, opportunities, and threats faced by the study program in order to improve its competitiveness at the national and international levels. The results of the study show that the quality of teaching staff and the relevance of the curriculum are the main strengths of the study program, while limited resources are a significant challenge. The study program also has the opportunity to strengthen cooperation with the Islamic financial industry and local government, although there is a threat from competition with similar, more established study programs. This study concludes that strengthening cooperation with industrial institutions, verifying funding sources, and increasing operational efficiency through digital technology are key strategies that need to be implemented. The implications of this study provide guidance for study program managers in determining strategic policies to maintain the sustainability and relevance of study programs in the future.